The chemotactic swimming behavior of bird schistosome miracidia in the presence of compatible and incompatible snail hosts - Marszewska, Anna; Cichy, Anna; Bulantová, Jana; Horák, Petr; Żbikowska, Elżbieta (PeerJ, 2020)
No effective method has yet been developed to prevent the threat posed by the emerging disease—cercarial dermatitis (swimmer’s itch), caused by infective cercariae of bird schistosomes (Digenea: Schistosomatidae). In our previous studies, the New Zealand mud snail—Potamopyrgus antipodarum (Gray, 1853; Gastropoda, Tateidae)—was used as a barrier between the miracidia of Trichobilharzia regenti and the target snails Radix balthica. Since the presence of non-indigenous snails reduced the parasite prevalence under laboratory conditions, we posed three new research questions: (1) Do bird schistosomes show totally perfect efficacy for chemotactic swimming behavior? (2) Do the larvae respond to substances emitted by incompatible snail species? (3) Do the excretory-secretory products of incompatible snail species interfere with the search for a compatible snail host? The experiments were carried out in choice-chambers for the miracidia of T. regenti and T. szidati. The arms of the chambers, depending on the variant, were filled with water conditioned by P. antipodarum, water conditioned by lymnaeid hosts, and dechlorinated tap water. Miracidia of both bird schistosome species chose more frequently the water conditioned by snails—including the water conditioned by the incompatible lymnaeid host and the alien species, P. antipodarum. However, species-specific differences were noticed in the behavior of miracidia. T. regenti remained more often inside the base arm rather than in the arm filled with water conditioned by P. antipodarum or the control arm. T. szidati, however, usually left the base arm and moved to the arm filled with water conditioned by P. antipodarum. In conclusion, the non-host snail excretory-secretory products may interfere with the snail host-finding behavior of bird schistosome miracidia and therefore they may reduce the risk of swimmer’s itch.
Keywords: Trichobilharzia spp.; Potamopyrgus antipodarum; Lymnaeid hosts; Miracidia; Chemo-orientation